Efficacy and Mechanism of Trimebutine Maleate Combined with Lactulose in the Treatment of Constipation-Predominant Irritable Bowel Syndrome in the Elderly. (11th November 2022) - Zhou, Yeping; Yang, Dujuan; Gu, Wenjun
Abstract : Objective . Study on the efficacy and mechanism of trimebutine maleate combined with lactulose in the treatment of constipation-predominant irritable bowel syndrome (IBS-C) in the elderly. Methods . From March 2019 to March 2021, 102 elderly patients with IBS-C were randomly divided into the observation group (51 cases) and the control group (51 cases). The observation group was treated with trimebutine maleate combined with lactulose, while the control group was treated with lactulose. Comparison of the clinical effects of the two groups. Comparison of vasoactive intestinal peptide (VIP) levels, neuropeptide Y (NPY) levels, and quality of life scores before and after treatment between the two groups. Documentation of adverse reactions during treatment. Results . The improvement of clinical symptoms in the observation group was significantly better than that in the control group, and the difference is statistically significant (P < 0.05 ). The level of VIP after treatment in the observation group was significantly lower than that in the control group and before treatment, and the differences were statistically significant (P < 0.05 ). The level of NPY after treatment in the observation group was significantly higher than that in the control group and before treatment, and the differences were statistically significant (P < 0.05 ). The scores of dietary restrictions and health worries in the control group after treatment were significantly higher than those before treatment, and the differences were statistically significant (P < 0.05 ). The scores of anxious, behavioral conflict, dietary restrictions, health worries, social response, and family relationship in the observation group after treatment were significantly higher than those in the control group and before treatment, and the differences were statistically significant (P < 0.05 ). There were no serious adverse effects in either group during the treatment period, with some patients experiencing dizziness and dry mouth, which improved after discontinuation of the drug, without special intervention. Conclusion . Trimebutine maleate combined with lactulose can improve clinical symptoms and quality of life in elderly patients with IBS-C, and its mechanism of action may be related to the regulation of the body's VIP and NPY levels.